ISOLATION OF SQUALENE FROM DICHLOROMETHANE EXTRACT OF CROTON NIGRITANUS LEAF (FUDMA JOURNAL OF SCIENCES, 2024)
A precursor of steroids with a variety of biological activities is squalene. The purpose of the study was to identify and describe the industrial/medical chemical found in Croton nigritanus. Using the solvents such as; dichloromethane, ethyl acetate, and n-hexane, the procedure entails a liquid-liquid extraction stage using the partition method and a solid-liquid extraction step using the maceration method. For separation and purification, gravity column chromatography (GCC) and thin-layer chromatography were employed. The isolated chemical's identity was determined using FTIR, 1H NMR and GC-MS spectroscopy. The inquiry successfully extracted and analyzed the major chemical compound which was identified as Squalene.
Keywords: Isolation; Terpenes; Croton; Extraction; Spectroscopy